Multi-objective Whale Optimization Algorithm and Optimal Area Product Model based Design of Litz-wire Gapped High-Frequency Transformer for LLC Resonant Converters - Ahmed, Daniyal; Wang, Li; Dai, Zehua (IEEE Energy Conversion Congress and Exposition, 2020)
This paper presents an improved resource-efficient multi-objective optimization methodology for the design of a Litz-wire based gapped high-frequency transformer (LHFT) for use in the LLC resonant converters. The method is based on a combination of the nature-inspired multi-objective whale-optimization algorithm (MOWOA) and the analytical optimal area-product model (OAPM). The aim is to obtain the best LHFT design for the LLC converter in a reduced number of iterations and time, with optimized total loss and volume, integrated magnetizing inductance, and the temperature-rise within limits. The proposed method's accuracy and efficient utilization of resources are proven through comparison with the existing benchmark optimization methods. Finally, experimental results are presented for validation by developing a 200W prototype LHFT for a 400VDC/12VDC LLC converter.